DAMPAK KEBIJAKAN PEMBANGUNAN DI DESA PINAMORONGAN KECAMATAN TARERAN KABUPATEN MINAHASA SELATAN - RARANTA, TESALONIKA; LENGKONG, FLORENCE DAICY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2020)
The central government allocates Village funds to support the development in Pinamorongan Village, Tareran District, South Minahasa Regency. However, in the course of the Village Fund, there are still indications of problems related to what is generated, the lack of development from the non-physical side to improve the welfare of the community and in improving the quality of life in the Village. This research uses a qualitative approach. Data obtained from interviews, observations and documents. Data analysis was performed through data reduction, data display, conclusion drawing. The findings of this study are that the development carried out by the Village Government sourced from Village funds in the Pinamorongan Village of the Tareran District has a positive and negative impact on the economic, social and environmental fields. The Pinamorongan Village Government should first determine and consider the goals and focus of the development that will be carried out and provide opportunities for people who are able to be involved in the development project as well as the ongoing maintenance of the facilities and infrastructure that has been built as well as replanting trees in the Watuleley tourist site. .Â Keywords: Impact of Policies, Village Development, Village Funds